RI BPK Audit Control Analysis of State Findings and Losses - Pramono, Agus Joko (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This research is quantitative research with descriptive and inferential statistical analysis using SPSS software. Inferential analysis in this study was performed using ordinal logistic regression. The research population is a timely audit report and has obtained BPK's opinion from 2019/2020 on the financial statements of local governments throughout Indonesia for the fiscal year. The findings show that the weakness of the accounting and reporting control system (KSPAP) and the weakness of the revenue and expenditure budget implementation control system (KSPPAPB) have a negative effect on the provision of BPK's opinion on the fairness of local government financial statements, the weakness of the internal control structure (KStPI) has no effect on the provision of BPK's opinion. on the fairness of the financial statements. The findings of state losses and the value of state losses have a negative effect on BPK's opinion on the fairness of financial statements. These findings are caused by other fictitious expenditures or procurements, lack of volume of work and/or goods, expenditures that do not match or exceed provisions and others. So that the greater the weakness of the case findings and the value of non-compliance found, the lower the level of fairness of the financial statements.